Faktor-Faktor Yang Berhubungan Dengan Kejadian Anemia Pada Ibu Hamil - Lestari, dwi lestari; Zakiah, Zakiah; Isnaniah, Isnaniah (JURNAL KEBIDANAN BESTARI, 2021)
According to data from the World Health Organization (WHO), the prevalence of anemia in pregnant women was 41.8% (WHO, 2010). The prevalence of anemia in pregnant women in Indonesia increased compared to 2013, in 2013 as many as 37.1% of pregnant women were anemic while in 2018 it increased to 48.9% (Riskesdas, 2018). The purpose of this study was to determine the factors associated with the incidence of anemia in pregnant women. This research method uses a literature study method taken from 10 articles, 3 international articles and 7 national articles. The analysis in this study uses thematic analysis.The results of the study of 10 articles, it was found that the incidence of anemia worth between 11.8% - 62%, age at risk worth between 24% - 71.8%, third trimester gestation age worth between 51% - 62.5%, risk parity worth between 6.1% - 57.7%, gestation interval <2 years worth between 5% - 53.5%, and malnutrition status worth between 31.4% - 58%. Of the 8 articles 6 articles 75% stated that there was a relationship between age and the incidence of anemia and 2 articles 25% stated that there was no relationship between age and the incidence of anemia, from 2 articles 100% that discussed gestational age stated that there was a relationship. gestational age with the incidence of anemia, of the 9 articles there were 5 articles 55.5% which stated that there was a relationship between parity and the incidence of anemia and 4 articles 44.5% which stated that there was no relationship between parity and the incidence of anemia, of 3 articles, there are 2 articles 66.6% which state that there is a relationship between pregnancy distance and the incidence of anemia and 1 article 33.4% states that there is no relationship between pregnancy interval and the incidence of anemia, from 4 articles 100% that discuss parity states that there is a relationship between parity and the incidence of anemia. There is a relationship between age, gestational age, parity, gestational distance and nutritional status with the incidence of anemia in pregnant women.